Peer Reviews on Development Finance Statistics Lessons learnt from seven pilots - Benn, Julia (OECD Development Co-operation Working Papers, 2020)
Countries often face similar challenges in statistical reporting on development finance. Through Peer Reviews on Development Finance Statistics, Development Assistance Committee (DAC) members and non-DAC providers, together with the OECD, jointly assess how countries collect, report and disseminate data on their development co-operation. These reviews help countries cope with an increasing demand for comprehensive, reliable and accessible statistics on development finance, in a context of frequent changes to the reporting requirements, staff-turnover and often complex, decentralised reporting systems. In the period from 2017 to 2019, the OECD conducted seven reviews (Australia, Canada, Denmark, France, Norway, Sweden and Switzerland). The Peer Reviews on Development Finance Statistics have proven to be useful and enriching for all participants, identifying several recommendations on how to improve the quality and use of development finance data. Building on the findings from the seven reviews, this working paper shares lessons learnt, including best practices, strengths and challenges